2001
DOI: 10.1046/j.1524-4741.2001.007001008.x
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Carcinoma of the Breast: A Population-Based Study of Nodal Metastases at Presentation and of Patterns of Relapse

Abstract: Tubular carcinoma of the breast (TCB) is a recognized histologic variant of infiltrating ductal carcinoma (IDC) and has been considered to have a comparatively favorable prognosis. However, previous studies have been based on small numbers of cases, some pure TCB and some mixed histology, or have not employed an appropriate comparison group. In this study 171 pure TCB cases and a comparison group of 386 cases with grade I (well differentiated) IDC were identified in a population-based database maintained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
5
24
1
3
Order By: Relevance
“…This is the first report describing therapeutic and clinical aspects in an unselected population insofar as previous studies have concentrated on the prognostic significance of various biological or clinical characteristics, such as radiotherapy after mastectomy [15], adjuvant anthracycline therapy [16], or histopathological type [17]. …”
Section: Discussionmentioning
confidence: 99%
“…This is the first report describing therapeutic and clinical aspects in an unselected population insofar as previous studies have concentrated on the prognostic significance of various biological or clinical characteristics, such as radiotherapy after mastectomy [15], adjuvant anthracycline therapy [16], or histopathological type [17]. …”
Section: Discussionmentioning
confidence: 99%
“…TC comprises of 0.7%-10.3% of the invasive epithelial breast cancer (IEC) and is more likely to occur in postmenopausal women. A populationbased study of nodal metastases with 171 TC patients has found the proportion of cases with axillary nodal involvement at presentation to be lower in TC than in the grade 1 IDC group (12.9% and 23.9%, respectively) [2]. A smaller study (n = 33) review *Correspondence to: Dr R. Yerushalmi, Division of Medical Oncology, British Columbia Cancer Agency, 600 W 10th Avenue, Vancouver, British Columbia, Canada V5Z 4E6.…”
Section: Good Prognosis Er Positivementioning
confidence: 99%
“…Niepowodzenia miejscowe po leczeniu chirurgicznym występują bardzo rzadko [1,12]. Z tego powodu oraz z uwagi na fakt, iż nowotwór rozpoznawany jest w niskim stopniu zaawansowania, niektórzy autorzy uważają, że nowotwór ten jest idealnym wskazaniem do leczenia oszczędzającego [5,10].…”
Section: Wstępunclassified
“…Ponadto rzadziej dochodzi do rozwoju niepowodzeń miejscowych oraz przerzutów odległych. Wszystkie te czynniki wskazują, że cewkowy rak piersi jest nowotworem o dobrym rokowaniu [5,[12][13][14]. Obserwowane 10-letnie przeżycia wynoszą 80-90% [5,15].…”
Section: Wstępunclassified